Obstetrical Management of Dystocia due to Schistosoma Reflexus in A Murrah Buffalo - Sahu, Uttam Kumar; Warghat, Chinmay; Newton Biswas; Renu Sharma; Neelam Kalasua; Brijesh Kumar (Animal Reproduction Update, 2024)
A very rare birth defect called Schistosomus reflexus (SR) causes the thoracic and abdominal organs to be exposed. The foetus also has a lot of spinal angulation, which makes the vertebral column curve in a clear way at the bottom. Ruminants most frequently exhibit reflexus (Bezek and Frazer, 1994), while various species have reported the pres- ence of a congenital schistocoelia (Pivnick et al., 1998). SR has been frequently reported in cattle, buffalo, and occa- sionally in sheep, goats, and other species (Robert, 1971; Rajoria et al., 2023) with an occurrence of 0.01 to 1.3% (Sloss, 1967; Knight, 1996) worldwide. SR occurs as early as the post-gastrulation embryo and involves the intermedi- ate mesoderm. This condition belongs to a family of defor- mities involving failure of complete closure of the ventral aspect of the fetal body wall. In humans, thoraco-abdomi- nal syndrome (TAS) displays striking similarities with the SR monster (Pivnick et al., 1998). Furthermore, there is a possibility of a genetic cause in which the fetus carriesrecessive genes from dam as well as sire, leading to defec- tive embryonic development. However, only the cases that display both visceral exposure and spinal inversion are considered true SR (Laughton et al., 2005). The exact aeti- ology of this anomaly is unknown, but it may be due to genetic factors, mutations, chromosomal anomalies, infec- tious agents, environmental factors, or a combination of all these factors (Noakes et al., 2019).
Keywords: Dystocia; Buffalo; Schistosoma reflexus; Congenital disorder